Hubungan Antara Fatique (Kelelahan) Dengan Stres Pada Perawat di Era Pandemi Covid-19 di RS X - Mulyadi, Egi (PT. Alahyan Publisher Sukabumi, 2024)
Coronavirus Disease 2019 or Covid19 is a new type of coronavirus that in addition to having an impact on the body, it can also have a serious impact on people's mental health. The incidence of Covid-19 cases continues to increase every day, and due to the increasing workload and concerns for their health and family, health workers as the frontline are increasingly frustrated. The purpose of this study is to determine the relationship between fatique (fatigue) and stress in nurses in the era of the covid 19 pandemic at Hospital X 2021. The sample used was 88 nurses. This study uses an observational analytical method with a cross-sectional design. Data collection was carried out by interviews, surveys and questionnaire distribution. The data analysis technique used is the chi-square test. The results of this study found that there was a relationship between fatique (fatigue) and stress in nurses in the era of the covid 19 pandemic at Hospital X 2021. The researcher is further advised to measure the level of work stress of nurses in the pandemic era not only from fatigue but also the factors that affect and cause work stress, which in this study has not been done by the author due to the limited time of the author's research, so that the research becomes more in-depth.